Evaluation of the genotoxicity effect and antioxidant response of two nanoparticles in Eisenia andrei - Correia, Bruno Ricardo da Silva (2014)
In the last few years there has been a growth in the nanotechnology industry. The increase in the discovery and production of new nanomaterials, were the nanoparticles are included, makes their release in the environment more likely. Although in the recent years there has been an increase of published studies related to the toxic effects of these materials, the information available is not enough since a large number of nanomaterials exist. Even though the soils are extremely important for life, there is a lack of toxicity studies available. Taking this in consideration, more studies using the terrestrial compartment are needed. For these studies, earthworms are a recommend species since standard guidelines for toxicity tests in soil using earthworms have been used with success for more than 30 years and this species is essential for the maintenance of properties of this compartment. The aim of our work was to determine if different concentrations of two distinct types of nanoparticles, one inorganic (titanium silicon oxide- TiSiO4) and other organic (sodium dodecyl sulphate/didodecyldimethylammonium bromide- SDS/DDAB), are genotoxic and also if there is an antioxidant response in terrestrial organisms. For this, earthworms from the species Eisenia andrei (weight: from 300 to 600mg) were exposed for 30 days to the“Organisation for Economic Co-operation and Development”(OECD) artificial soil contaminated with different concentrations of the tested nanoparticles. After the exposure, coelomocytes were extracted from earthworms and DNA damage was assessed by comet assay. In addition the activity of antioxidant enzymes (e.g. glutathione peroxidase, glutathione reductase and glutathione-S-Transferase) was assessed, as well as lipid peroxidation. The results have shown that both particles were genotoxic, specially the TiSiO4-NPs. Taking in consideration available information about the mechanism by which the nanoparticles can exert their toxicity, it was expected that the genotoxicity would be related with an increase with the production of reactive oxygen species,leading to alterations in the activity of the antioxidant enzymes and the products of lipid peroxidation. Although some alterations could be found in the activity of antioxidant enzymes and in lipid peroxidation, these results are not statistically significant, suggesting that both nanoparticles are capable of causing damage to the DNA, but the mechanism used by these particles might not related with oxidative stress.